PENERAPAN KONSELING BEHAVIORISTIK DENGAN TEKNIK SHAPING UNTUK MENINGKATKAN KEDISIPLINAN BELAJAR PADA PESERTA DIDIK SMP N 2 NALUMSARI - Muhamad Nur Safi'an; Gudnanto Gudnanto; Sumarwiyah Sumarwiyah (Universitas Muria Kudus, 2022)
The aims of this study are: 1. To describe behavioristic counseling with shaping techniques in improving students' learning discipline at SMP N 2 Nalumsari, 2. To find out the factors that hinder students' learning discipline at SMP N 2 Nalumsari. Learning discipline is a form of obedience, obedience, regularity of students in learning. In this study, the shaping technique is used to form new behavior that has never been carried out before by giving reinforcement. The type of research used is a case study of guidance and counseling. And 2 subjects who have a lack of discipline in studying at SMP N 2 Nalumsari. The results of this study indicate that the counseling process at SMP N 2 Nalumsari has been able to form new behavior for the counselee so that the counselee tries to maintain and continue to make changes that are formed, namely obeying existing rules or regulations, having a spirit of respecting time, being able to manage study time at home, being diligent and regularly in learning, paying attention when lessons take place in the classroom, carrying out the tasks and obligations they receive in a timely manner. The conclusion is that the application of Behavioristic counseling with the Shaping technique at SMP N 2 Nalumsari is positive, can improve student learning discipline and get a good response from students.